Apical cytoskeletons and junctional complexes as a combined system in epithelial cell sheets. Issue 1 (1st August 2017) - Yano, Tomoki; Kanoh, Hatsuho; Tamura, Atsushi; Tsukita, Sachiko
Abstract: Epithelial cell sheet formation is central to many aspects of vertebrate development and function. For example, it is a major principle of differentiation in embryogenesis and regeneration, enables the compartmentalization of tissues, and is the basis for the maintenance of homeostasis throughout the body. A key characteristic of biologically functional epithelial cell sheets is a clear difference between the top and bottom sides owing to the apicobasal polarity of the cells in the sheet, as seen in the simple polar epithelia. Epithelial cell sheets are formed by cell–cell adhesion conferred by junctional complexes, in particular via tight junctions (TJs), which thus create a paracellular barrier. This review focuses on the apical side of the sheet, which serves as the front line. The apical membranes and TJs of the various tissues have specific characteristics that enable them to function and adapt to their biological context: each system must be robust, but also dynamic and flexible to maintain homeostasis. Here, we describe various apical cytoskeletal structures that are critical to the integrity of epithelial cell sheets. We also discuss the association of apical cytoskeletal networks with TJs, which thus forms a combined system, tentatively termed the TJ–apical complex .